Correction to: RiseTx: testing the feasibility of a web application for reducing sedentary behavior among prostate cancer survivors receiving androgen deprivation therapy - Linda Trinh; Kelly P. Arbour-Nicitopoulos; Catherine M. Sabiston; Scott R. Berry; Andrew Loblaw; Shabbir M. H. Alibhai; Jennifer M. Jones; Guy E. Faulkner (BMC, 2018)
Following publication of the original article [1], the author has requested us to make a correction in the Results section of the Abstract and in the Discussion sections as explained below: